El simbolismo del poncho de cacha y su incidencia en los procesos comunicacionales del pueblo puruhá cacha del canton riobamba durante el periodo 2004-2014 - Allauca Carmilema, Rolando (2016)
The research consists of five chapters well done and with justification, which have been instrumental in breaking down the thesis topic formulated. In the first chapter the problem statement, objectives, starting from the general to the specific, and finally the importance of the subject are detailed described. However, in this part it sets out the study and each edge of the research project described. The second chapter the theoretical framework, the scientific and conceptual support of the treaty issue, the same highlighting issues Cacha, types of sweaters, their colors and their use as a communication process is cited within the parish and the society. It also includes the Andean symbolic representations, the iconography in Indian textiles. To this it stands implying symbolism poncho as Cacha affects communication processes in the villagers Cacha. The following section contains design Chakana (ancient iconography) present in the poncho. The Andean Cross unit code communication between the symbolic universe socio-cultural and agricultural life governed by natural cycles. Finally the importance of why Cacha is considered "Cradle of Ecuadorian Nationality" contextualized from its history, traditions, customs and cultural heritage of the country described. The third chapter demonstrates the methodological process used in research, thus explains the collection and analysis of data investigated in the field, the same who helped develop new knowledge to strengthen it. The Four chapter sets out the conclusions that were reached, after making a systematic process of research. It is noted that after analyzing the findings were able to establish appropriate recommendations, which can be accepted by the authorities and inhabitants of the Cacha parish, students of the career of Social Communication of the National University of Chimborazo (UNACH), and the historians.